Pembelajaran Hasta Karya dan Wiraswasta Berbasis Potensi Lokal Model Project Based Learning (PjBL) di SMA Muhammadiyah Sokaraja - Rusmiyati Rusmiyati; Sriyanto Sriyanto (UM Purwokerto Press, 2023)
Today's teacher-centered learning is not suitable for students to prepare for their lives, therefore it must be changed to student-centered learning. In Hasta Karya and Entrepreneurial Learning based on local excellence in class XI SMA Muhammadiyah Sokarja the teacher uses the Poject Based Learning (PjBL) learning model. The Project Based Learning model has a goal so that students are more active when participating in class lessons, are more independent in practicing, are more disciplined when learning and practice responsibility. Teacher-centered learning causes students to be inactive, student productivity decreases so that learning outcomes decrease. Therefore in creating learning in the classroom the teacher must be more creative and innovative. In carrying out project based learning based on local excellence, students carry out learning together in their groups which are carried out collaboratively in heterogeneous groups. The products that have been produced by students are in the form of business proposals or business proposals, packaging logos and batik products typical of the Sokarja region based on local potential as well as small business practices selling batik products in school cooperatives.